2017
DOI: 10.1111/jppi.12206
|View full text |Cite
|
Sign up to set email alerts
|

Trauma‐Informed Day Services: An Initial Conceptualization and Preliminary Assessment

Abstract: Trauma-informed care (TIC) is a systems-focused philosophy of service delivery based upon principles of choice, collaboration, empowerment, safety and trustworthiness that recognizes the pervasive impact of trauma across the human experience. In a grassroots effort, one organization developed an innovative, trauma-informed day program to meet the needs of individuals with intellectual and developmental disabilities (IDD) who were recently deinstitutionalized. The present study is intended to provide an initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
(54 reference statements)
0
22
0
Order By: Relevance
“…This was part of a larger research project that utilized a mixed‐methods approach to obtain a preliminary understanding of the impact of TIC within intellectual/developmental disabilities services. Additional details of the study can be found elsewhere (Keesler & Isham In press ). The present findings are an analysis of staff perspectives, understandings and experiences with TIC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was part of a larger research project that utilized a mixed‐methods approach to obtain a preliminary understanding of the impact of TIC within intellectual/developmental disabilities services. Additional details of the study can be found elsewhere (Keesler & Isham In press ). The present findings are an analysis of staff perspectives, understandings and experiences with TIC.…”
Section: Methodsmentioning
confidence: 99%
“…familial abandonment, restrictive interventions and lengthy institutionalization) and complex behavioural needs. A brief overview of the programme is presented here yet described in greater detail elsewhere (Keesler & Isham In press ).…”
Section: Introductionmentioning
confidence: 99%
“…Trauma‐informed care can be implemented with both correctional staff and counselors. According to Keesler and Isham (), it can take a while for trauma‐informed care to become a part of the culture within a setting. However, when a facility adapts a trauma‐informed care approach, the whole facility may be working to help offenders address their trauma through these five principles, which can create a more holistic approach to help offenders and to reduce trauma‐provoked incidents.…”
Section: Trauma‐informed Carementioning
confidence: 99%
“…Higher education and higher ranked personnel (e.g., administration) were associated with more favorable ratings of TIC. Keesler and Isham (2017) identified the feasibility of integrating TIC within the context of services for individuals with intellectual and developmental disabilities. Findings suggested a positive association between TIC and staff satisfaction, restraint reduction, and behavioral improvement among individuals with disabilities.…”
Section: Growth and Advancementmentioning
confidence: 99%